Endozoochory by Goats and White-Tailed Deer: Type of Ruminant Affect Recovery and Germination of Neltuma pallida Seeds - Salinas Marcos, Jorge; Cruz Luis, Juancarlos Alejandro; Aguirre, Lucrecia (Preprints.org / MDPI, 2025)
The "algarrobo", Neltuma pallida is a key tree species in the seasonally dry tropical forests in Equatorial Pacific South America, currently at risk. Its regeneration depends on endozoochorous seed dispersal, in which seeds are ingested and later defecated by animals, helping to release and scarify them. This study compared the role of the native white-tailed deer (Odocoileus virginianus) and the introduced goat (Capra hircus) in seed dispersal. Seeds were recovered from the dung of both species after experimental feeding and from free-ranging goats grazing in fruiting N. pallida forests. Seed recovery was higher in deer dung (9.4%) than in goat dung (3.1%). Retention time was also shorter in deer (peak at 48 hours) than in goats (peak at 84 hours). Only deer scarification significantly improved germination percentage (Tukey test, p < 0.001) and germination speed (T25 = 8.98 days). Goats reduced germination speed under experimental conditions (T25 = 19.25 days), but slightly improved it under forest conditions (T25 = 12.81 days). These differences are attributed to the morphophysiological traits of each species. Although goats did not enhance overall germination, they maintained it at ~44% and contributed to seed dispersal and dormancy release.